Influence of Highland and production-oriented cattle breeds on pasture vegetation: a pairwise assessment across broad environmental gradients - Pauler, Caren; Isselstein, Johannes; Braunbeck, Thomas; Schneider, Manuel K. (Agriculture, ecosystems & environment, 2019)
Highland cattle are lighter, slower-growing and less demanding on forage than most production-oriented cattle breeds, which may affect vegetation composition. This study aimed at identifying the importance of breed-dependent impact on the composition of pasture vegetation in comparison to well-investigated factors such as site properties and grazing management. Vegetation was investigated in 50 paired pastures at 25 locations ranging from Swiss mountain areas to lowlands in southern Germany. Pastures in a pair had been grazed by either Highland cattle or a more production-oriented cattle breed for at least 5 years. Plant species composition was assessed on 150 subplots, three per pasture in areas representing different grazing intensities. Generalized linear mixed-effects models, (partial) constrained correspondence analysis and structural equation models were used for data analysis. Despite similar site conditions between the paired pastures at each location, plants on pastures of Highland cattle showed significantly lower indicator values for grazing and trampling tolerance. Both, grazing and trampling were strongly connected and had a common negative effect on plant species diversity. Moreover, Highland cattle had a direct positive influence on diversity, likely due to reduced woody plant species cover and a higher cover of epizoochoric species. This resulted in significantly higher plant species richness (alpha and gamma) on pastures of Highland cattle than those of production-oriented breeds. The observed differences in plant species richness between pastures of different grazing breeds increased with duration of adaptation, i.e. the time a pasture was grazed by a certain breed. The study demonstrates a clear impact of cattle breed on vegetation, which is consistent with the phenotypical differences of the animals. Largely overlooked, cattle breed may explain some of the frequently contrasting responses of vegetation to grazing. The findings have important implications for management decisions and breeding endeavours which go beyond mere productivity objectives. They highlight the potential of low-production Highland cattle to sustain and promote ecosystem services on species-rich, semi-natural grasslands.
Gesehen am 15.01.2020